Analisis Jalur Faktor - Faktor yang Mempengaruhi Penerimaan Rumah Tangga Tani Miskin di Kabupaten Bantul - Nanik Dara Senjawati (Jurnal Dinamika Sosial Ekonomi, 2000)
Poverty, a lack situation was signed by the attitude and behavior, that is showed in a bad quality of human resources, the low of exchange value for production, low productivity, limitted of capital, and low of households income. The research results show that the farm household income was directly influenced by capital, working hours, market accessibility, family size, supervision, and small trading. The increase of capital, working hours, along with market accessibility was raising of income, especially for the households those getsuppervision on small trading. The number of family member who was participating in the household activity are very important to increase the income and the capability of households in capital accumulation.Key words: Path analysis, households income, small farmer's